Pengaruh Brand Awareness Dan Brand Loyalty Terhadap Keputusan Pembelian Produk Teh Pucuk Harum (Studi Kasus Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Tahun 2018 Di Universitas Islam Malang) - Suriyanto Suriyanto; Agus Widarko; Arini Fitria Mustapita (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to determine the effect of brand awareness and brand loyalty on purchasing decisions for fragrant shoots (a case study on economics and business students in 2018 at the Islamic University of Malang). The type of research used is explanatory research with the method of distributing questionnaires. The sample in this study revealed 70 respondents and data processing using the SPSS computer program. This study has met the requirements of validity and reliability. Analysis of the data used in this study is the classical assumption test, statistical test, and analysis of the coefficient of determination. The variable used in this study is the dependent variable on purchasing decisions, and the independent variables are brand awareness and brand loyalty. The results of this study indicate that simultaneously there is a positive and significant effect. Partially, it is shown that the variables of Brand Awareness and Brand Loyalty have a positive and significant effect on the Purchase Decision variable for the case study of fragrant shoots tea products for students of the economics and business faculty in 2018 at the Islamic University of Malang. Keywords: Brand Awareness, Brand Loyalty, Purchase Decision.